UJI HASIL KINERJA MESIN PENGOLAH FILM OTOMATIS MINI MEDICAL - Raharjo, Oky Didik; Azam, Much.; Ketut Umiati, Ngurah Ayu (BERKALA FISIKA, 2006)
Have been researched result test of Mini Medical automatic processing film machine. The research is conducted by reforming X-ray toward the film in the cassette which there is stepwedge on it, film catharsis is then performed using automatic processing film machine. After generating radiograph, its density is measured, and then we count speed index, fog index and contrast index. This activity is conducted every day for seven days in succession. Based on the index of fog and contrast film, the result of the research indicates that the work result of automatic processingn film machine on the first until fifth day is still in the allowed limits, but on the sixth and seventh day it exceeds the permitted limits. This is due to the ability of generator solution is getting lower (solution pH is getting smaller). Mean while, its speed index for seven days is still in the permitted limits. Â Keywords : Result test, automatic processing film machine, stepwedge, fog,Â contrast